Relevansi Pemikiran Ekonomi Sheikh Daud Al-Fatani dengan Kontrak Pembiayaan Perbankan Islam - Towpek, H.; Borhan, J. T. (Universiti Sains Islam Malaysia, 2024)
Furu‘ al-Masa’il is among Sheikh Daud al-Fatani’s writings that concludes almost all main topics of fiqh including fiqh al-mu‘amalat. It is directly related to economic and finance as what it is understood nowadays. Therefore, this writing attempts to identify the relevance of Syeikh Daud economic thoughts as what has been elaborated in his transaction chapter with Malaysian Islamic banking practices with special concern on financing contracts. This writing applies the content analysis and analysis of relevancy methods. Basically, an analysis of relevance is based on ‘link and match’ by conceptual and operational definitions, and by legitimation and/or classification aspects. This writing finds out that Syeikh Daud economic thoughts has relevance with project financing contracts in Malaysian Islamic banking.